2019
DOI: 10.1177/0333102419828994
|View full text |Cite
|
Sign up to set email alerts
|

Complete withdrawal is the most effective approach to reduce disability in patients with medication-overuse headache: A randomized controlled open-label trial

Abstract: Background Medication-overuse headache leads to high disability and decreased quality of life, and the best approach for withdrawal has been debated. Aim To compare change in disability and quality of life between two withdrawal programs. Methods We randomized medication-overuse headache patients to program A (two months without acute analgesics or migraine medications) or program B (two months with acute medications restricted to two days/week) in a prospective, outpatient study. At 6 and 12 months, we measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 30 publications
2
19
0
3
Order By: Relevance
“…(2011), MOH was consistently shown to be associated with a lower QoL score compared to healthy controls, episodic headache, and most importantly chronic daily headache without medication overuse. It has subsequently been shown that quality of life improved after withdrawal (Nielsen et al., 2019). In our study, we saw an improvement in perceived overall quality of life and health in all three arms which is in line with the last‐mentioned study.…”
Section: Discussionmentioning
confidence: 99%
“…(2011), MOH was consistently shown to be associated with a lower QoL score compared to healthy controls, episodic headache, and most importantly chronic daily headache without medication overuse. It has subsequently been shown that quality of life improved after withdrawal (Nielsen et al., 2019). In our study, we saw an improvement in perceived overall quality of life and health in all three arms which is in line with the last‐mentioned study.…”
Section: Discussionmentioning
confidence: 99%
“…A recent randomized trial in the outpatient setting by the Danish Headache Center provided evidence that abrupt withdrawal of all acute treatments was more effective in reducing disability and more feasible for patients than gradual withdrawal, while both programs resulted in reduced disability and increased QoL 96,97 …”
Section: Managing the Headache Patient With Medication Overusementioning
confidence: 99%
“…At the end of the recruitment for the RCT, we started the open-label trial in which participants were assigned to standardised acute drug withdrawal. This arm was added to provide a pragmatic, non-parallel comparison with acute drug withdrawal, which is considered the most effective treatment of CM with MO (18). The reason why it was not added as one further arm of the double-blind part of the study is because results would have been biased by the lack of any active or sham tDCS procedure, and therefore would have not been comparable.…”
Section: Methodsmentioning
confidence: 99%